Magnetic resonance imaging in patients with granulomatosis with polyangiitis (Wegener's) and subglottic stenosis - Klink, Thorsten; Holle, Julia; Laudien, Martin; Henes, Frank Oliver; Moosig, Frank; Platzek, Corinna; Adam, Gerhard; Gross, Wolfgang Ludwig; Bley, Thorsten Alexander (Magnetic Resonance Materials in Physics Biology and Medicine, 2013)
Objective: To evaluate the ability of MRI to detect subglottic stenosis and to differentiate between active and inactive subglottic inflammation in patients with granulomatosis with polyangiitis (GPA). Materials and methods: MRI studies of the larynx of 18 GPA patients with suspected SGS were included. The MRI protocol included T1- and T2-weighted and STIR-sequences, dynamic contrast enhancement (DCE) and diffusion weighted imaging (DWI). Two independent observers reviewed the MR images. SGS were identified and quantified, inflammatory activity was assessed using edema imaging, DCE and DWI. Final MRI diagnoses were compared to the clinical, laryngoscopic and histopathologic results. Results: MRI confirmed SGS in all GPA patients with significant narrowing of the airway lumen and thickening of subglottic wall. Assessing the subglottic inflammatory activity, MRI showed a sensitivity of 87.5 % and a specificity of 60.0 %. Interrater agreement was κ = 0.769. Of the different MR technical approaches tested, edema imaging was most sensitive and specific. DWI led to significant differences in the apparent diffusion coefficient between active and inactive subglottic inflammation. No significant differences were found with DCE imaging. Conclusion: MR imaging has shown the ability to detect and grade SGS in patients with GPA. It non-invasively assesses the status of inflammatory activity utilizing edema sensitive sequences and DWI. © 2012 ESMRMB.
CRIS-Team Scopus Importer:2024-12-04
Keywords: Granulomatosis with polyangiitis; Magnetic resonance imaging; Subglottic stenosis; Wegener's granulomatosis